Molecular Epidemiological Characterization and Health Burden of Thalassemias in the Chaoshan Region, People's Republic of China. (3rd March 2016) - Zheng, Xiangbin; Lin, Min; Yang, Hui; Pan, Mei-Chen; Cai, Ying-Mu; Wu, Jiao-Ren; Lin, Fen; Zhan, Xiao-Fen; Luo, Zhao-Yun; Yang, Hui-Tian; Yang, Li-Ye
Abstract: Thalassemia is one of the most prevalent inherited disease in southern China. However, there have been only a few epidemiological studies of thalassemia in the Chaoshan region of Guangdong Province, People's Republic of China (PRC). A total of 6231 unrelated subjects in two main geographical cities of the Chaoshan region was analyzed for thalassemia. Seven hundred and thirty-six cases of suspected thalassemia carriers with microcytosis [mean corpuscular volume (MCV) <82.0 fL] were found by complete blood cell (CBC) count, and were tested by reverse dot-blot gene chip to reveal a total of 331 mutant chromosomes, including 278 α-thalassemia (α-thal) alleles and 53 β-thalassemia (β-thal) alleles. The most common α-thal mutations were the Southeast Asian (– – SEA ), followed by the –α 3.7 (rightward) and –α 4.2 (leftward) deletions. The two most common β-thal mutations were HBB : c.316-197C>T and HBB : c.126_129delCTTT, accounting for 69.81% of the β-thal defects in the studied individuals. In addition, a rare mutation, Cap +1 (A>C) ( HBB : c.-50A>C) was described for the first time in the Chaoshan region. Our results gave a heterozygote frequency of 5.31% for common α- and β-thal in the Chaoshan region, and also indicated a higher prevalence of thalassemia with a heterozygote frequency of 6.29% in Chaozhou, followed by Shantou (3.37%). This study provided a detailed prevalence and molecular characterization of thalassemia in the Chaoshan region, and will be valuable for developing a strategy for prevention of thalassemia and reducing excessive health care costs in this area.